Identifikasi Kandungan Formalin Pada Bakso Dalam Upaya Meningkatkan Kesehatan Masyarakat di Desa Sarimulyo Kecamatan Cluring Kabupaten Banyuwangi - Anggita Endah Setiarini; Silmi Fadhila; Sekar Dewi Indriyani; Afan Abdur Rohman; Kartika Adi Saputra; Ashfa Annindya Hazrida; Kevin Mubarok; Putu Alisya Fernanda Putri Winata; Sefri Ton; Dani Agung Wicaksono (Fakultas Teknik Universitas Cenderawasih, 2023)
Meatballs are meat processed foods that are widely circulated and favored by the public, in addition to their delicious taste, meatballs also have relatively affordable prices. Because meatballs are much-loved by the community, there are not a few meatball traders who take actions that result in health hazards with the aim that the meatballs that are sold can last longer and be able to increase profits, one of which is using the preservative formaldehyde where formalin is a food additive that is prohibited by the Food and Drug Administration. government. So that with this PKM activity it is able to increase public knowledge, especially PKK mothers in Sarimulyo Village, Banyuwangi Regency about the dangers of formaldehyde to health and how to detect meatballs containing formaldehyde.